Selective precolumn derivatization of fatty acids with the fluorescent tag 6‐aminoquinoline and their determination in some food samples by reversed‐phase chromatography. Issue 12 (23rd February 2017) - Jonnada, Murthy; El Rassi, Guadalupe Davila; El Rassi, Ziad
Abstract : Fatty acids (FAs) have been selectively derivatized with a fluorescent tag, 6‐aminoquinoline (6AQ), which yielded fluorescent FA‐6AQ derivatives that have excitation (λexc = 270 nm) and emission (λemi = 495 nm) wavelengths that are farther apart. This precolumn derivatization is characterized by its simplicity occurring at room temperature between the carboxylic acid group of the FA and the amino group of 6AQ in the presence of a nonaqueous soluble carbodiimide coupling agent such as the N, N´ ‐dicyclohexylcarbodiimide. The FAs extracts are readily derivatized in chloroform and can be analyzed without any further sample cleanup that minimizes sample loss. The FA‐6AQ derivatives derived from standard FAs as well as from extracted FAs from food samples were separated by reversed phase chromatography on a homemade naphthyl methacrylate monolithic (NMM) column and C4 silica‐based column. While the NMM column provided excellent separation for saturated FA‐6AQ derivatives, the C4 silica column was able to separate simultaneously saturated and unsaturated FA‐6AQ derivatives. The MNN column permitted the analysis and quantitation of the saturated FA‐6AQ derivatives extracted from coconut oil. The C4 column provided the selectivity needed to analyze and quantify saturated and unsaturated derivatized with 6AQ and extracted from meat. The limits of detection and quantitation were 5 and 20 nM, respectively, with a linear dynamic range extending from 20 nM to 40 μM. The 40 μM upper limit was due to the limited solubility of the FA‐6AQ derivatives in the diluting mobile phase, which is the initial mobile phase used in gradient runs.